2010
DOI: 10.1007/s10765-010-0718-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Vapor–Liquid Equilibrium for the DME + Diisopropyl Ether Binary System and Correlation for the DME + CO2 + Diisopropyl Ether Ternary System

Abstract: Vapor-liquid equilibrium (VLE) data have been measured with a statictype VLE apparatus for the dimethyl ether (DME)-diisopropyl ether (DIPE) binary system at five temperatures within the range from 293.04 K to 352.70 K. An isothermal correlation for the experimental data has been carried out based on the Peng-Robinson equation of state. The regressed binary interaction parameters were used to estimate VLE for the DME-CO 2 -DIPE ternary system at 298.15 K. From the study, it is demonstrated that DIPE is an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Owing to the concentration of unreacted calcium acetate still increased with the initial concentration of calcium acetate aqueous solution, this promotion was enhanced, and consequently the crystallization conversion as well as acetic acid extraction ratio increased. However, with the initial concentration increased, the interaction between acetate ions and calcium ions at high initial concentration becomes stronger, so promotion of low concentration is more significant than the high concentration of calcium acetate. Therefore, the extent of the increase in crystallization conversion and acetic acid extraction ratio at the high initial concentration was less than the extent of the decrease at the low initial concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the concentration of unreacted calcium acetate still increased with the initial concentration of calcium acetate aqueous solution, this promotion was enhanced, and consequently the crystallization conversion as well as acetic acid extraction ratio increased. However, with the initial concentration increased, the interaction between acetate ions and calcium ions at high initial concentration becomes stronger, so promotion of low concentration is more significant than the high concentration of calcium acetate. Therefore, the extent of the increase in crystallization conversion and acetic acid extraction ratio at the high initial concentration was less than the extent of the decrease at the low initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The acetic acid concentration in the organic phase was titrated against a standard NaOH solution using anhydrous ethanol as diluent. Moreover, the solubility of CO 2 in TBP at a temperature range of 30 °C to 90 °C and CO 2 partial pressure of up to 4.5 MPa, were measured by the constant volume method with a set of experimental apparatus as reported by Wu et al …”
Section: Methodsmentioning
confidence: 99%
“…Gui et al also concluded that the ether groups in the absorbents for CO 2 may be advantageous to promote the absorption ability based on their experimental data. Thus, various researchers have paid attention to the solubility data for the CO 2 + ether absorbent systems. Using the isothermal synthesis method, Gui et al , determined CO 2 solubilities in six diethylene glycol ethers and two ethylene glycol ethers at 288.15–318.15 K and 0–6 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Their results clearly indicate that TEGDME is the best solvent for CO 2 removal among these 14 absorbents. Solubility data of CO 2 in the ether absorbents such as dibutyl ether, diisopropyl ether, and dimethyl ether + diisopropyl ether were determined at 263.15−309.15 K and 0−3 MPa by Guo et al, 12 Zhu et al, 13 and Wu et al, 14 respectively. Miller et al 15 selected 15 volatile solvents including some ethers as CO 2 absorbents and determined CO 2 solubility data at 298.15 K and 0−5.3 MPa using the bubble-point method.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the VLE data for R152a + DMF and R152a + DMAC binary systems were measured using a static analytical method. The experimental apparatus is illustrated in Figure , and the detailed information has been described in the earlier papers. The apparatus consists of five systems: equilibrium system, temperature controlling system, injection and detection systems, data acquisition system, and vacuum system. And the main units are an equilibrium cell, an isothermal water bath, a temperature controller, a pressure transducer, six-way valves, a gas chromatography, a vacuum pump, a magnetism mixer, and a refrigerator.…”
Section: Experimental Sectionmentioning
confidence: 99%